PENGARUH PROFITABILITAS, RISIKO KEUANGAN, NILAI PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2009-2011) - Wahyu Chreestiyorini, 0935030705 (Students Journal of Accounting and Banking, 2013)
Income smoothing practices by management aimed at reducing the level of fluctuations in earnings resulting from the companys year-to-year by moving income from high-income year into periods that are less profitable. The purpose of this study was to determine the effect of profitability, financial risk, value and size of the companys corporate income smoothing practices.The population in this study are all companies listed on the Indonesia Stock Exchange during the study period of 2009-2011. The samples in this study were selected using purposive sampling method, which means withdrawal or randomly selecting samples that have specific goals or targets. Analysis tool used is logistic regression.The results showed that the variables profitability and corporate value not significant positive effect on income smoothing,while financial risk variables significant positive effect on income smoothing and firm size variable is not significant negative effect on income smoothing.Keywords: profitability, financial risk, value and size of the companys corporate income smoothing practices.